The impact of regulatory approval and Medicare coverage on outcomes of carotid stenting. Issue 7 (3rd December 2013) - Gray, William A.; Verta, Patrick
<x xml:space="preserve">Abstract</x> Background Carotid artery stenting (CAS) was introduced in the United States nearly a decade ago as a novel treatment of severe carotid stenosis. Voluminous and high‐quality prospective data permit analysis of longitudinal trends in CAS outcomes. Methods Outcomes from all prospective trials with the Food and Drug Administration (FDA) oversight from 2000–2011 were reviewed, as were the subset of studies using a single CAS system. All studies shared common inclusion/exclusion criteria, endpoints, independent assessment/adjudication of neurological events, and were conducted in accordance with FDA regulations. Death and stroke (DS) rates from FDA‐approved studies in high‐surgical‐risk patients were assessed. Results Between 2000 and 2011, two distinct periods with clustered and differentiated outcomes in CAS IDE trials were observed, separated by FDA approval and Centers for Medicare and Medicaid Services (CMS) coverage in 2004–2005. The mean 30‐day DS rate in the first wave (2000–2004) of CAS trials was 5.3% (95% CI: 4.6–6.2%), and fell significantly to 2.6% (95% CI: 1.9–3.7%; P = 0.0001) in the second wave (2006–2011). This decline occurred during a simultaneous, independent 24‐fold increase in monitored CAS activity. This decline in DS rates was observed in symptomatic and asymptomatic patients, alike independent of device tested. Conclusions Declines in periprocedural DS rates in CAS appear linked to regulatory and coverage approvals leading to increased operator experience along with continued regulatory oversight, and provide insight into the introduction of other novel therapies. © 2013 Wiley Periodicals, Inc.